Ain`t just imagination! Effects of motor imagery training on strength and power performance of athletes during detraining - Dello Iacono, A. Y.; Ashcroft, K.; Zubac, D. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to investigate the effects of motor imagery (MI) training on strength and power performances of professional athletes during a period of detraining caused by the COVID-19 outbreak. Methods: Thirty male professional basketball players (age, 26.1 ± 6.2 yr) were randomly assigned to three counterbalanced groups: two MI training groups, who completed imagery training by mentally rehearsing upper and lower limb resistance training exercises loaded with either 85% of one repetition maximum (85%1RM) or optimum power loads (OPL), or a control group. For six consecutive weeks, although all groups completed two weekly sessions of high-intensity running, only the MI groups performed three additional MI sessions a week. Maximal strength and power output were measured through 1RM and OPL assessments in the back squat and bench press exercises with a linear positioning transducer. Vertical jump and throwing capabilities were assessed with the countermovement jump and the seated medicine ball throw tests, respectively. Kinesthetic and visual imagery questionnaires, and chronometry and rating of perceived effort scores were collected to evaluate MI vividness, MI ability, and perceived effort. Results: Physical performances improved significantly following both MI protocols (range, ~2% to ~9%), but were reduced in the control group, compared with preintervention (P = 0.016). Moreover, interactions (time-protocol) were identified between the two MI groups (P = 0.001). Whereas the 85%1RM led to greater effects on maximal strength measures than the OPL, the latter induced superior responses on measures of lower limb power. These findings were mirrored by corresponding cognitive and psychophysiological responses. Conclusions: During periods of forced detraining, MI practice seems to be a viable tool to maintain and increase physical performance capacity among professional athletes.